Himalaya : vanishing cultures - Reynolds, Jan, 1956- (San Diego : Harcourt Brace Jovanovich, 1991)
Describes the customs and day-to-day life of a family living in the Himalaya Mountains.
Keywords: Himalaya Mountains Region -- Juvenile literature. -- Juvenile literature; Himalaya Mountains Region -- Juvenile literature. -- Pictorial works -- Juvenile literature; Himalaya Mountains Region -- Social life and customs